THE EFFECT OF COMPENSATION ON EMPLOYEE SATISFACTION AT PT. BANK SULSELBAR MAKASSAR - Panggalo, Yana Sari; Sambara, Kordiana; Jaya, Amir (Entrepreneurship Undergraduate Program at Amkop Business School, 2025)
This study aims to analyze the effect of compensation on employee satisfaction at PT. Bank Sulselbar Antang Branch Office. The research method used is a quantitative approach with Spearman Rank correlation analysis techniques, coefficient of determination (R²), and t-test. The research sample consisted of 17 employees selected using the census technique. The results of the analysis show that compensation has a significant effect on employee satisfaction, where salary, benefits, incentives, and bonuses are the main factors that increase job satisfaction. These findings indicate that a fair and competitive compensation system contributes to increasing employee motivation and loyalty. Thus, companies need to strengthen compensation policies to improve employee welfare and overall organizational productivity.